2009
DOI: 10.1007/s10535-009-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

Apomeiotic pollen mother cell development in the apomictic Boechera species

Abstract: Pollen mother cell (PMC) development in the apomictic Boechera species B. holboellii, B. gunnisoniana and B. divaricarpa were investigated by various cytological methods. In prophase I, in triploid species B. holboellii and B. gunnisoniana the individual chromosomes condensed into long strands within the nucleus. Then, in metaphase I, each PMC formed a restitutional nucleus thereby bypassing the rest of the first meiotic division. This is interpreted as representing apomeiosis. Subsequently, the restitution nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…For example, aposporous apomict pseudogamous Panicum maximum conserved the 2m:1p ratio, as only one, unreduced polar nucleus contributes from the female while fertilization provides a reduced male gamete (Savidan 2000). The 2m:1p endosperm ratio is conserved in apomictic pseudogamous triploid Boechera holboellii in a different way, since only unreduced female and male gametes participate in a viable seed development (Taskin et al 2009). In contrast, most apomicts in Paspalum, including P. notatum, form endosperms with a 4m:1p ratios.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…For example, aposporous apomict pseudogamous Panicum maximum conserved the 2m:1p ratio, as only one, unreduced polar nucleus contributes from the female while fertilization provides a reduced male gamete (Savidan 2000). The 2m:1p endosperm ratio is conserved in apomictic pseudogamous triploid Boechera holboellii in a different way, since only unreduced female and male gametes participate in a viable seed development (Taskin et al 2009). In contrast, most apomicts in Paspalum, including P. notatum, form endosperms with a 4m:1p ratios.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…The life cycle of flowering plants involves the alternations of a diploid sporophytic and haploid gametophytic phase (Li et al 2009, Taskin et al 2009. Microsporogenesis occurs at the end of the sporophytic phase and undergoes a clearly defined cell division program resulting in a gametophyte (pollen grain) comprising the generative and vegetative cells.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the B. holboellii accession seed samples yielded 2C and 6C peaks (4m:2p), while in one accession (BH1) 2C and 5C peaks were obtained (15). In our previous work on pollen mother cell (PMC) development in Boechera, we found that B. holboellii show an altered male gametophyte development: the unreduced gametes are produced by apomeiosis at a high frequency (32). Therefore, in triploid apomictic Boechera species, the 2m:1p ratio is apparently achieved by fertilization of two unreduced polar nuclei (2n:3m) with an unreduced sperm (2n:3p) to yield 6m:3p endosperm.…”
Section: Resultsmentioning
confidence: 93%